2020
DOI: 10.1186/s12955-020-01466-1
|View full text |Cite
|
Sign up to set email alerts
|

Preference of individuals in the treatment strategies of acute myocardial infarction in China: a discrete choice experiment

Abstract: Background: Acute myocardial infarction (AMI) is a significant cause of mortality and morbidity worldwide. Today, with increasing life quality and social economy, people pay much attention to the cost-effectiveness of a treatment strategy. This study investigated the preferences of individuals who would be potential caregivers or patients for AMI treatment in order to provide liable and instructive information for cardiologists and other related physicians. Methods: A discrete choice experiment was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Latent class analyses found 3 distinct groups with varying preferences based on treatment cost, treatment duration, and mortality risk. 21 Muhlbacher et al conducted a DCE to evaluate patient preferences for medication options following ACS. 22 These authors also found reduction in mortality to be the most important attribute, followed by prevention of new MI.…”
Section: Discussionmentioning
confidence: 99%
“…Latent class analyses found 3 distinct groups with varying preferences based on treatment cost, treatment duration, and mortality risk. 21 Muhlbacher et al conducted a DCE to evaluate patient preferences for medication options following ACS. 22 These authors also found reduction in mortality to be the most important attribute, followed by prevention of new MI.…”
Section: Discussionmentioning
confidence: 99%
“…The theory is not only applicable to economics but is also widely used in other disciplines, such as in industries, education, software, and medical care [ 33 , 34 ]. Medical applications include prenatal diagnostic testing and myocardial infarction diagnostic testing [ 35 ]. We conducted the questionnaire survey and VR game experience and then collected the corresponding statistical data based on the results that were collected [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on completing the questionnaire prior to VR application and pretesting the VR, participants were allowed 20 minutes to complete the research. An interactive design was devised; when the cursor or fingers touch the nouns (perceived remission rate, probability of adverse events), volunteers will see the introduction around the concepts and gain some useful information about them [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular disease is the greatest threat to human health worldwide, and myocardial infarction is the leading cause of death ( 1 , 2 ). The burden of myocardial infarction is growing because of the increasing prevalence of myocardial infarction risk factors, as well as high morbidity and mortality rates associated with myocardial infarction ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%